Assessing Tax Reform as a Journey to Tax Administration - Aribowo, Irwan; Kamilah, Niswatun Nurul; Kumar, Jai; Rofi'ah, Laily (KnE Social Sciences, 2022)
This study examined whether the initiatives carried out by the Directorate General of Taxation (DGT) as part of a series of tax reforms have met the characteristics of the six building blocks in the development of Tax Administration 3.0 as formulated by the OECD. The research was conducted using a literature review of the tax reform volume III that is being implemented by the DGT and of the Tax Administration 3.0 model developed by the OECD. The data in this study were secondary data collected from various reports and studies. There were several findings, including about a large number of characteristics in the ”established” phase towards Tax Administration 3.0 that were carried out and designed by the DGT. However, there were some building-block characteristics that require collaboration with other parties and so which need to be a concern of the government, such as the single identity number project for digital identification, the implementation of the pay as you earn (PAYE) system in the daily life of taxpayers, and a governance framework to increase the involvement of various stakeholders in tax administration. Keywords: OECD, Tax Administration 3.0, tax reform